Teachers' awareness of health issues and health protecting activities - Sochenko Y.A (Kharkov National Pedagogical University, 2012)
The paper analyzes the results of the teachers' survey on health problems and health protecting activities. It shows the insufficient level of the teachers' awareness of the notions of health, healthy lifestyle, health protection, and health protecting technologies. It proves the importance of teachers' professional health formation, the necessity to develop a system of professional training on the basis of theoretical and methodological concepts of health protecting activities. In research took part 95 teaches of Saki, Simferopol and Kerch.